Costos de producción del cacao y su incidencia en la rentabilidad del agricultor - González Tumbaco, Bryan Josue (2025)
Ecuador has become one of the largest exporters of cocoa in Latin America, which has caused the production of this fruit to be more demanding in both quantity and quality. This visible growth in the marketing chain has given more opportunity to cocoa intermediaries, since they, due to their greater purchasing power, buy cocoa at a lower cost than stipulated in the market because they assume various costs. The cocoa producer, not having an efficient cost system in his production, puts him at disadvantages, since they do not know the profitability of each harvest and end up giving in to the pressure in selling with the intermediary.......